Improving the fat content of foods - Williams, Christine (CRC Press LLC, 2011)
Discusses ways of reducing saturated fatty acids in food, explores how to develop and use PUFAs as functional ingredients, and covers ways of improving the sensory quality of product incorporating modified fats.